(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Chronic gastroduodenitis (CGD) in the structure of diseases of the digestive organs belong to the most common pathology of childhood with progressive growth exceeding 100 cases per 1000 children. For comparison, according to A.B. Mazurin in 1989, the prevalence of this pathology was recorded at the level of 79 cases per 1000 children under the age of 14. In addition to a distinct upward trend in detectable HCG, which averages 10% per year, there is a tendency to aggravate the course not only due to an increase in the specific gravity of erosive, subatrophic and atrophic forms, but also due to polymorbid flow with the presence of up to 2 or more concomitant diseases. As the most frequent comorbid conditions of HCG, a number of authors indicate violations of the trophological status (dyslipidemia, changes in the musculoskeletal and cardiovascular systems, a high frequency of autonomic dysfunctions, dysbiotic disorders. The presence of frequent concomitant changes on the part of other organs and systems in children with HCG raises the question of the existence of uniform pathogenetic mechanisms in which HCG is considered as a pathological process involving an integral organism with a violation of metabolic processes, homeostatic parameters, regulatory circuit, intestinal endoecology, and, accordingly, the optimality of the development of a growing organism. Such a complex of changes leads to a decrease in the adaptive capabilities of the child’s body with subsequent changes in behavioral reactions and social relations, which goes beyond the scope of gastroenterological pathology proper